TableMaker: An Excel Macro for Publication-Quality Tables - Hlavac, Marek (Journal of Statistical Software, Code Snippets, 2016)
This article introduces TableMaker, a Microsoft Excel macro that produces publicationquality tables and includes them as new sheets in workbooks. The macro provides an intuitive graphical user interface that allows for the full customization of all table features. It also allows users to save and load table templates, and thus allows layouts to be both reproducible and transferable. It is distributed in a single computer file. As such, the macro is easy to share, as well as accessible to even beginning and casual users of Excel. Since it allows for the quick creation of reproducible and fully customizable tables, TableMaker can be very useful to academics, policy-makers and businesses by making the presentation and formatting of results faster and more efficient.